1993
DOI: 10.1002/ps.2780380219
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of spray droplets to foliage: The role of dynamic surface tension and advantages of organosilicone surfactants

Abstract: Measurements of the dynamic surface tension of seven surfactants (four organosilicones, two ‚conventional’︁ hydrocarbon‐based surfactants and an organosilicone + hydrocarbon‐based blend; 0.5 to 5.0 g litre−1) have been combined with data on the adhesion of their spray droplets to pea leaf. The latter were determined by a method enabling the surface age, and thus surface tension of the droplets at impact, to be calculated. Adhesion was directly related to the dynamic reduction in surface tension (2 to 50 mN m−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 23 publications
0
40
0
3
Order By: Relevance
“…O Silwet L-77 tem um bom coeficiente de eficácia, reduzindo rápido a tensão superficial, corroborando com os resultados obtidos por Stevens et al (1993).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…O Silwet L-77 tem um bom coeficiente de eficácia, reduzindo rápido a tensão superficial, corroborando com os resultados obtidos por Stevens et al (1993).…”
Section: Resultsunclassified
“…A tensão superficial é um dos fatores chaves na performance dos surfatantes e sua redução é mais importante do que o tamanho da gota, velocidade da gota e ângulo de incidência na folha para a determinação da adesão nas folha (Stevens et al, 1993).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Organosilicone surfactants can reduce the surface tension of spray droplets more significantly than other surfactants, but their effect on spray droplet VMD is not consistent in the published literature. Stevens et al (32,33) reported that the VMD of spray droplets with organosilicone surfactants can be reduced to a significantly greater degree than conventional surfactants, but Holloway et al (25) actually observed the opposite effect in that VMD of droplets increased significantly when organosilicone surfactants were used. The different spray nozzles and spray pressure, as well as other ingredients in the spray solution, could be the cause of the observed discrepancy.…”
Section: Surfactantsmentioning
confidence: 96%
“…Since the rate of diffusion to the droplet surface tends to be inversely related to molecular size [9], the diffusion coefficient of monoterpene alcohols in water is much higher than surfactant. This property allows a reduction in surface tension in 2-3 ms of relatively high VMD droplets that are flattened on impact, and a reduction in their bounce.…”
Section: Contact Anglementioning
confidence: 99%